Old wine in new bottles: Kaempferol is a promising agent for treating the trilogy of liver diseases. (January 2022) - Xiao, Xiaolin; Hu, Qichao; Deng, Xinyu; Shi, Kaiyun; Zhang, Wenwen; Jiang, Yinxiao; Ma, Xiao; Zeng, Jinhao; Wang, Xiaoyin
Abstract: As a source of various compounds, natural products have long been important and valuable for drug development. Kaempferol (KP) is the most common flavonol with bioactive activity and has been extracted from many edible plants and traditional Chinese medicines. It has a wide range of pharmacological effects on inflammation, oxidation, and tumour and virus regulation. The liver is an important organ and is involved in metabolism and activity. Because the pathological process of liver diseases is extremely complicated, liver diseases involving ALD, NASH, liver fibrosis, and HCC are often complicated and difficult to treat. Fortunately, there have been many reports that KP has a good pharmacological effect on a series of complex liver diseases. To fully understand the mechanism of KP and provide new ideas for its clinical application in the treatment of liver diseases, this article reviews the pharmacological mechanism and potential value of KP in different studies involving various liver diseases. In the trilogy of liver disease, high concentrations of ROS stimulate peroxidation and activate the inflammatory signal cascade, which involves signalling pathways such as MAPK/JAK-STAT/PERK/Wnt/Hipp, leading to varying degrees of cell degradation and liver damage. The development of liver disease is promoted in an inflammatory environment, which is conducive to the activation of TGF-β1, leading to increased expression of pro-fibrosis and pro-inflammatory genes. Inflammation and oxidative stress promote the formation of tumour microenvironments, and uncontrolled autophagy of cancer cells further leads to the development of liver cancer. The main pathway in this process is AMPK/PTEN/PI3K-Akt/TOR. KP can not only protect liver parenchymal cells through a variety of antioxidant and anti-apoptotic mechanisms but also reduces the immune inflammatory response in the liver microenvironment, thereby preventing cell apoptosis; it can also inhibit the ER stress response, prevent inflammation and inhibit tumour growth. KP exerts multiple therapeutic effects on liver disease by regulating precise signalling targets and is expected to become an emerging therapeutic opportunity to treat liver disease in the future. Graphical Abstract: The role of kaempferol in the progression of the trilogy of liver disease ga1